Instagram Addiction : Narcissism and Fear of Missing Out (FoMO) - Virga Virena Suwandi; Hafied Cangara; Umaimah Wahid (Jurnal Mantik, 2022)
This study aims to determine the relationship between Fear of Missing out (FoMO) and addiction to social media Instagram in adolescents. Fear of Missing out is the fear of losing valuable moments of individuals or other groups while social media addiction is excessive use or dependence on social media, in this study, Instagram. This study uses a systematic literature review (SLR) method. conclusions were drawn by conducting a review of a total of 14 journals, with the keywords Fear of Missing Out and Instagram social media addiction. The results showed that the higher the FoMO, the higher the level of social media addiction, and the relationship between fear of surveillance and social media addiction. Suggestions for youth to manage their own access to social media by carrying out other activities such as participating in extracurricular activities at school.